The Influence Of Work-Life Balance And Workload On Work Commitment And Its Impact On Employee Performance At Dinas PUPR Pidie (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to examine the Work-Life Balance and Workload impact on Employee Performance in Dinas PUPR Pidie with Work Commitment as a Mediator. The population was 241 civil servants (ASN) at the Dinas PUPR Pidie. The sample was the entire population, namely 241 respondents. Data were analyzed using the Structural Equation Modeling (SEM). Results revealed that at the Dinas PUPR Pidie, Work-Life Balance influences Work Commitment, Workload influences Work Commitment, Work-Life Balance does not influence employee performance, Workload affects employee performance, Work Commitment influences employee performance, Work Commitment fully mediates the Work-Life Balance impact towards Employee Performance, and Work Commitment partially mediates the Workload impact towards Employee Performance at the Dinas PUPR Pidie. These findings define that the work commitment model acts as a mediator but is different for work-life balance and workload in influencing employee performance. By revealing all the results, it is clear that the model in this research has proven that increasing employee performance has an impact on work-life balance, suitability of workload, and strengthening work commitment.